Enhancing maize yield, water use efficiency, and Zn content under drought stress by applying Zn-solubilizing bacteria - Fahimeh Khaledi; Hamidreza Balouchi; Mohsen Movahhedi Dehnavi; Amin Salehi (Agricultural Water Management)
Mitigating drought stress is important for corn production. One way to alleviate drought stress and increase yield is to use supplementary Zn and Zn-solubilizing bacteria. The objective of this study was to investigate the effects of ZnSO4 combined with rhizosphere bacteria on the yield, Zn uptake, relative water content (RWC), and water use efficiency (WUE) of corn under drought stress. A field experiment was conducted with sufficient irrigation, moderate stress, and the application of different combinations of ZnSO4 and Zn-solubilizing bacteria. These combinations included four levels without Zn, with Zn applied to foliage, soil, or seed priming, and three levels of bacteria (without bacteria, Pseudomonas fluorescens, and P. aeruginosa). Drought stress decreased RWC by 11 %, the cobs/m2 by 9 %, and increased WUE by 5.7 % in corn. However, priming or foliar application of ZnSO4 with both P. fluorescens and P. aeruginosa strains increased the number of cobs/m2 by 12.5 % and the number of rows/cob by 15 %. Additionally, most methods of applying ZnSO4 and bacteria increased the number of grains, 100-grain weight, grain yield, and WUE of corn. The results showed a 48 % and 52 % increase in 100-grain weight with the foliar application of ZnSO4 and P. aeruginosa, respectively, under normal and drought conditions compared to the control. Soil application of ZnSO4 without bacteria or foliar application of ZnSO4 with P. aeruginosa enhanced grain and biological yield by 48 % and 8.9 % under drought stress, respectivly. Similarly, under sufficient irrigation, Zn seed priming with P. aeruginosa increased grain yield by 39.6 % and biological yield by 14.9 % compared with the control. Drought stress and foliar application of ZnSO4 with P. fluorescens and P. aeruginosa increased the Zn content of corn leaves and grains. In conclusion, although drought decreased corn performance, foliar or priming of ZnSO4 with Pseudomonas bacterial strains improved yield.